Opportunities and Challenges for Investors Investing in Metro City - Nazeri Nazeri (Westscience Press, 2023)
Metro City, as one of the developing cities in Indonesia, offers a variety of attractive investment opportunities. This article discusses the investment opportunities available in Metro City, such as the property sector, industry and promising economic growth potential. However, this article also highlights some of the challenges faced by investors, including regulatory, infrastructure and competition issues. With a deeper understanding of investment conditions in Metro City, investors can take wise steps in exploiting its economic growth potential. The research method used in this research is a qualitative approach whose research design is descriptive, namely providing an accurate picture or explanation of the problems faced. Descriptive research is research carried out to determine the value of independent variables, either one or more variables (independent) without making comparisons, or connecting them with other variables. This research describes the opportunities and challenges for investors investing in Metro City.